KEBIJAKAN PELAYANAN KEPADA NARAPIDANA DAN TAHANAN DI LEMBAGA PEMASYARAKATAN GLENO MUNICIPIO ERMERA TIMOR-LESTE - Lucia De Jesus Martins; Soesilo Zauhar; Endang Setyowati (Universitas Tribhuwana Tunggadewi, 2015)
Penitentiary, or usually called LAPAS, is a place to foster inmates and detainees who experience the crisis of morality, reasoning and law awareness in the independence age of Timor-Leste. Research attempts to describe and to analyze the services provided for inmates and detainees at Gleno Penitentiary of Timor-Leste and also to examine the supporting and constraining factors. Result of research indicates that the implementation of services and fostering for inmates and detainees at Gleno Penitentiary is already conforming to the existing rules but several factors still influence the delivery of services such as lacking of human resource, structure and infrastructure, overcapacity and budget. It is recommended to the Ministry of Justice, through National Directorate of Penitentiary and Social Reintegration, to recruit adequate number of wardens, to improve the reliability of structure and infrastructure, to provide permanent medical staffs in Penitentiary, or to allocate additional budget from the government.